The many faces of Alexander Hamilton : the life and legacy of America's most elusive founding father - Ambrose, Douglas, 1957-; Martin, Robert W. T. (Robert William Thomas), 1967- (New York University Press, 2006)
Revolutionary War officer, co-author of the Federalist Papers, our first Treasury Secretary, Thomas Jefferson's nemesis, and victim of a fatal duel with Aaron Burr: Alexander Hamilton has been the focus of debate from his day to ours. On the one hand, Hamilton was the quintessential Founding Father, playing a central role in every key debate and event in the Revolutionary and Early Republic eras. On the other hand, he has received far less popular and scholarly attention than his brethren. Who was he really and what is his legacy?Scholars have long disagreed. Was Hamilton a closet monarchist or a sincere republican? A victim of partisan politics or one of its most active promoters? A lackey for British interests or a foreign policy mastermind? The Many Faces of Alexander Hamilton addresses these and other perennial questions. Leading Hamilton scholars, both historians and political scientists alike, present fresh evidence and new, sometimes competing, interpretations of the man, his thought, and the legacy he has had on America and the world.